Risk Management in the Analysis of Failures of Protective Coatings in Municipal Sewage Treatment Plant Tanks - Janusz Banera; Marek Maj; Ahmad H. Musa (Buildings)
Polyurea failures in reinforced concrete tanks, such as swimming pools and sewage treatment plants, require a thorough analysis of the causes of failures during renovation. Urban agglomerations are increasingly relying on these facilities for maintaining city functioning, and the increasing concentration of pollutants in these facilities necessitates urgent repairs due to frequent failures. More thorough analysis should be given to repeated failures on the same object or “twin” objects within a short period, causing high renovation costs and long shutdowns. The causes of failures can be found not only as a result of insufficient knowledge but also in a limited analysis of the entire project from the assumption phase to completion. The article analyzed water and sewage tanks on which failures of applied polyurea coatings occurred many times. The posteriori uses of the risk management analysis with the assessment of the impact and probability of occurrence of the planned activities that failed allows it to be applied a priori and treated as a necessary analysis. For this purpose, in selected repairs, those activities that had the greatest impact on failure and a relatively high probability of occurrence during implementation were distinguished from the entire project. Based on the risk management analysis, it was shown that the basic cause of the failure was the poor knowledge and insufficient experience of the entities performing the repairs, and the errors that occurred could be minimized by conducting good diagnostics of the facility, selecting professional designers and contractors, and constant monitoring of each important activity.